Drosophila suzukii Management in Latin America: Current Status and Perspectives - Garcia, Flávio Roberto Mello; Lasa, Rodrigo; Funes, Claudia Fernanda; Buzzetti, Karina (Entomological Society of America, 2022)
Spotted-wing drosophila, Drosophila suzukii Matsumura, was first established in Latin America in Mexico in 2011. The vinegar fly has since been detected in 296 municipalities in Argentina, Brazil, Chile, Mexico, and Uruguay. Drosophila suzukii is polyphagous and is found on 64 host plants in 25 families in Latin America, with most hosts also exotic species. In Latin America, D. suzukii is attacked by 14 species of parasitoid wasps in the families Diapriidae, Figitidae, and Pteromalidae, which are promising native parasitoids for control of the pest. This article analyzes results from studies on monitoring, biological, chemical, and cultural control, and sterile insect techniques to provide a basis for the development of area-wide and sustainable D. suzukii management programs in Latin America. The review examines how D. suzukii has been managed in Latin America and how research conducted in this region can contribute to management of the species in other parts of the world.